A Case Report on Angiomyxoma - Monayem, Farhana Binte; Parvin, Zebunnessa; Mahmud, Reaz; Ahmed, SK Abdul Momen (Faridpur Medical College Journal, 2014)
Aggressive Angiomyxoma (AA) is a rare variety of soft tissue tumour of pelvis and perineum occurring almost exclusively in adult females. AA is most often found in or in proximity to the lower pelvis, more specifically perineum, vulva, vagina or inguinal regions. Here we report a case of angiomyxoma. She is a 40 years old house wife, presented with a brownish, soft, multilocular, pedunculated nontender solid mass in the left side of the vaginal wall. Though initially it was provisionally diagnosed as a case of cervical polyp, ultimately histopathology proved it to be a case of Aggressive Angiomyxoma. DOI: http://dx.doi.org/10.3329/fmcj.v8i2.20396 Faridpur Med. Coll. J. 2013;8(2): 99-101